Entrepreneurship : Sulaman Kreatif Enterprise / Tuan Nurazamimah Tuan Hassan ... [et al.] - Tuan Hassan, Tuan Nurazamimah; Che Awang, Che Nor Zaini; Abd Halim, Nur Hasnizan; Mohd Did, Rahmat; Azami, Nur Ain (2008)
“Sulaman Kreatif Enterprise” is the name of our company. We will start operate our business on 1st January 2009. Our business based on selling of already prepared traditional clothes and receive booking from guest. Our company permanent address is located in B10, 7B Lorong Pandan Damai, 2/1 Pusat Komersial, 25159 Kuantan, Pahang.